Rizal without the overcoat in commemoration of Jose Rizal's 150th birth anniversary - Ocampo, Ambeth R. (Anvil Publishing, Inc., 2012)
" An updated and expanded edition of the best-selling title that offers fresh insights on the life and times of our National Hero. Here, Ocampo has succeeded where other historians have failed-- and that is in making the study and reading of Rizal not a burden, but a joy.??Publisher's description.